Suicide in The Light of Logotherapy in Social Work - Aldadi, Atheer Meshal; Atowieleme, Khadija Muqnea (Journal of Humanities & Social Sciences, 2022)
The social work profession is always seeking to keep up with the rapid developments that society is going through and has always developed its treatments, and methods; to suit the problems that develop and change with the change of society, and this article will discuss the phenomenon of suicide in the light of logotherapy, which is one of the modern treatments and trends in the practice of the social work profession , and the article calls for the orientation to employ the logotherapy with this category, and will be presented the concept of suicide, and the factors leading to it, its forms, classifications, and types, definition and genesis of logotherap , its philosophy, objectives, the assumptions on which logotherapy is based, the strategies and techniques used in it, and finally the professional intervention of logotherapy with individuals who have suicidal thoughts.